Nutritional conduct in the care of Polycystic Ovary Syndrome manifestations (Research, Society and Development, 2021)
The objective of this review was to evaluate the effects of nutritional patterns indicated for the management of Polycystic Ovary Syndrome (PCOS). For this purpose, a bibliographic search was carried out in the PubMed database, comprising articles published between 2018 and 2021, in English and Portuguese. A total of 1141 articles were found, and 610 articles were excluded for being unrelated to the topic studied or for not being freely available. Of the 531 articles, 41 were selected and 20 studies were included in the review. As a result, the studies suggest that nutritional interventions, such as low-carbohydrate (